Directions for educational development in the Year of the Teacher and Tutor - Veriaskina A. N., Sabodina E. P., Dzokaeva Z. M., Pokhilko A. D., Gubanova M. A., Sian I., Vlasova S. A., Dormidontov R. A., Omarov O. M., Ismailov S. O., Annaev R. I., Narykova O. N., Liakhova E. G., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Petrova N. G., Pogosian S. G., Zaritskaia V. V., Koreneva A. V., Ryzhkova I. V., Denisova O. A., Lekhanova O. L., Gudina T. V., Glukhova O. A., Bukin D. A., Zinin S. V., Tkachenko I. S., Panteleeva N. G. (Directions for educational development in the Year of the Teacher and Tutor, 2023)
the chapter reveals the potential of mentoring as a «personalized support strategy» based on the maximum actualization of the creative potential of teachers and students. The experience of organizing mentoring within the framework of the «teacher-teacher» model is described, and the main stages of the work are characterized. Mentoring in the «student-pupil» form is also considered. Using specific examples from our own practice, it is proven that this form can be most holistically implemented in the course of joint design and research activities of mentors and mentees.
Keywords: проектная деятельность; наставничество; наставник; project activities; mentor; mentoring; формы наставничества; наставляемый; целевая модель наставничества; персонифицированное сопровождение; forms of mentoring; mentee; target mentoring model; personalized support